Description of the immature stages of Saccharosydne subandina Remes Lenicov & Rossi Batiz (Hemiptera: Delphacidae) - Rossi Batiz, Maria Fernanda (2011)
The genus Saccharosydne Kirkaldy 1907 includes eight species, two of which are pests of sugarcane in tropical America and rice in Asia. Saccharosydne subandina Remes Lenicov & Rossi Batiz described from Argentina feedson pampas grass, garlic and rye in agricultural subandean areas of different provinces. This study provides informationon the immature stages of S. subandina, including a key for their separation, based on laboratory rearedspecimens and field observations.